2006
DOI: 10.1093/ptj/86.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Training of Balance Under Single- and Dual-Task Conditions in Older Adults With Balance Impairment

Abstract: Background and Purpose. Traditionally, rehabilitation programs emphasize training balance under single-task conditions to improve balance and reduce risk for falls. The purpose of this case report is to describe 3 balance training approaches in older adults with impaired balance. Case Descriptions. Three patients were randomly assigned to 1 of 3 interventions: (1) single-task balance training, (2) dual-task training under a fixed-priority instructional set, and (3) dual-task training under a variable-priority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
177
0
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(194 citation statements)
references
References 47 publications
4
177
0
13
Order By: Relevance
“…There is some evidence demonstrating that the dual tasking effects on postural control can be reduced with dual task training93, 139, 140 and one can extrapolate that similar effects should also be achievable for walking. Pilot data also support this idea 74, 141. For example, Toulotte et al trained 8 elderly non‐faller and 8 elderly fallers twice weekly for 3 months 74.…”
Section: Discussionmentioning
confidence: 96%
“…There is some evidence demonstrating that the dual tasking effects on postural control can be reduced with dual task training93, 139, 140 and one can extrapolate that similar effects should also be achievable for walking. Pilot data also support this idea 74, 141. For example, Toulotte et al trained 8 elderly non‐faller and 8 elderly fallers twice weekly for 3 months 74.…”
Section: Discussionmentioning
confidence: 96%
“…According to task coordination and learning theory, single-task training has fewer processing requirements compared with dual-task training and does not allow the patient to perform two tasks at the same time. However, dual-task training allows a patient to conduct more than two tasks simultaneously, enabling coordination of various tasks [7]. In a study conducted by Hiyamizu et al [8], the group that simultaneously performed recognition and movement tasks exhibited improved recognition task performance abilities, which showed that performing motor and recognition tasks at the same time affected one or both performances [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recientes estudios (Bouchard et al, 2011;Scott et al, 2011;Mayer et al, 2011), apuntan que la pérdida de la masa muscular relacionada a la edad, varía entre un 13 y 24% en adultos con hasta 60 años, y aumenta más de un 50 % en ancianos con edad por El conocimiento de las características funcionales del equilibrio en personas mayores, pueden promover el desarrollo de estrategias específicas de prevención de caídas, considerada el tipo más común de accidentes en personas mayores (Silsupadol et al, 2006), con vistas a la mantenimiento de la autonomía y la preservación de la independencia del anciano, durante el mayor tiempo posible.…”
Section: ____________________________________________________________unclassified